The influence of ovarian cyst type and size on ovarian reserve markers: implications for fertility counseling and preservation strategy - Sun, Xingyu; Liu, Doudou; Guo, Zijing; He, Lijuan; Wang, Shaohua (Frontiers in Endocrinology, 2025)
BackgroundOvarian cysts are common in reproductive-aged women and may affect ovarian reserve, thereby impacting fertility potential. This study aimed to evaluate the differential impact of various ovarian cyst types and sizes on ovarian reserve markers to inform individualized fertility care.MethodsA retrospective cohort study was conducted on 474 women classified into four groups: endometrioma, simple cyst, dermoid cyst, and controls without cysts. Serum anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH) levels, and antral follicle count (AFC) were assessed. Multivariate regression analyses adjusted for age and BMI were used to evaluate the independent effects of cyst type and size on ovarian reserve markers.ResultsCompared to controls, women with ovarian cysts had significantly lower AMH and AFC levels and higher FSH levels (all p < 0.001). Endometriomas exerted the most profound negative impact, with the lowest AMH and AFC values and the highest FSH levels. Larger cysts were independently associated with greater reductions in AMH and AFC and increases in FSH levels.ConclusionBoth ovarian cyst type and size significantly influence ovarian reserve. Endometriomas and larger cysts are particularly detrimental. These findings highlight the need for personalized fertility counseling and early preservation strategies in affected women.